Impact of cognitive performance on the functional capacity of an elderly population in Natal, Brazil Impacto do desempenho cognitivo na capacidade funcional em uma amostra populacional de idosos do nordeste brasileiro - Keithlen Cruz Moreira de Castro; Ricardo Oliveira Guerra (Arquivos de Neuro-Psiquiatria)
Functional incapacity and cognitive impairment are conditions related to the process of human aging. Cognitive impairment is considered an important predicitve factor for functional impairment in elderly populations. This cross-sectional study analyzes the association between cognitive performance and functional capacity in an elderly population sample in Natal, Brazil. A total of 213 elderly persons were assessed by the BOAS Multidimensional Questionnaire (Brazil Old Age Schedule) and the Mini-Mental State Examination (MMSE). The results of multivariate analysis and linear regression showed that age and schooling level are factors associated with cognitive performance in the elderly of this study. The final explicative model, elaborated by logistic regression, found that cognitive performance was the only predicitve variable of functional incapacity for the activities of daily living even when adjusted for sociodemographic variables. A incapacidade funcional e o déficit cognitivo são condições relacionadas com o processo de envelhecimento humano. O déficit cognitivo é considerado um importante fator preditor de prejuízos funcionais em populações idosas. Este estudo transversal analisa a associação do desempenho cognitivo na capacidade funcional de uma amostra populacional idosa residente em Natal-RN. Foram avaliados 213 idosos pelo Questionário Multidimensional-BOAS e pelo Mini-Exame do Estado Mental (MEEM). Através de analise multivariada mediante regressão linear, os resultados apontam a idade e o nível de escolaridade como fatores associados ao desempenho cognitivo nos idosos do estudo. O modelo explicativo final elaborado através de regressão logística apresentou o desempenho cognitivo como a única variável preditora de incapacidade funcional para as atividades da vida diária mesmo quando ajustado por variáveis sócio-demográficas.